2008
DOI: 10.1017/s0952675708001553
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic variability and grammatical knowledge: an articulatory study of Korean place assimilation

Abstract: The study reported here uses articulatory data to investigate Korean place assimilation of coronal stops followed by labial or velar stops, both within words and across words. The results show that this place-assimilation process is highly variable, both within and across speakers, and is also sensitive to factors such as the place of articulation of the following consonant, the presence of a word boundary and, to some extent, speech rate. Gestures affected by the process are generally reduced categorically (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…First of all, some proportion of CSD might involve complete deletion of /t/ rather than mere coarticulation with a following word. Several studies have found that in assimilatory sandhi processes, both categorical and gradient effects may be at play (Barry, 1985(Barry, , 1992Kochetov & Pouplier, 2008;Niebuhr et al, 2011;Nolan et al, 1996), suggesting that the variability of sandhi rules may not be entirely due to gradient gestural overlap or lessened gestural magnitude (see also Bermúdez-Otero, 2010, for discussion). Moreover, there is good evidence that gestural overlap itself is often planned, rather than just a surface result of temporal compression of gestures.…”
Section: Production Planning As An Explanatory Factormentioning
confidence: 99%
“…First of all, some proportion of CSD might involve complete deletion of /t/ rather than mere coarticulation with a following word. Several studies have found that in assimilatory sandhi processes, both categorical and gradient effects may be at play (Barry, 1985(Barry, , 1992Kochetov & Pouplier, 2008;Niebuhr et al, 2011;Nolan et al, 1996), suggesting that the variability of sandhi rules may not be entirely due to gradient gestural overlap or lessened gestural magnitude (see also Bermúdez-Otero, 2010, for discussion). Moreover, there is good evidence that gestural overlap itself is often planned, rather than just a surface result of temporal compression of gestures.…”
Section: Production Planning As An Explanatory Factormentioning
confidence: 99%
“…Although we did not specifically investigate C1-C2 differences for non-coronal sequences, the finding that the coronal constriction is either absent altogether (the overwhelming pattern), or fully present (in a small subset of tokens, mainly for Argentinian) is strongly suggestive of the intrinsically categorical status of place assimilation in the data (cf. Honorof [1999]; Martínez Celdrán and Fernández P lanas [2007] on Peninsular Spanish; see also Stephenson and Harrington [2002] on Japanese; Kochetov and Pouplier [2008] on Korean). In sum, the results largely support Hypothesis 2 (Categorical vs. Gradient Assimilation), as most of its specific predictions repeated in Table 12 (cf.…”
Section: Hypothesismentioning
confidence: 99%
“…Recent studies have shown that languages differ considerably in how they implement a given assimilation process. Moreover, within a given language, the details of a ssimilation often depend on many other factors, including the specific gestures involved, the type of boundary (morphological or prosodic), language-particular patterns of gestural coordination, speaking rate and/or style, word frequency, or speaker individual strategies ( Nolan 1992, Hardcastle 1994Holst and Nolan 1995 Farnetani andBusà 1994, Celata et al 2010 on Italian; Pallarès 2001, Solé 2002 on Catalan;Kochetov and Pouplier 2008 on Korean, among others). Yet, there is still little understanding of the underlying principles that determine the choice of assimilation types in any particular case of assimilation -as categorical, gradient, or partly-gradient and partly-categorical.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some sandhi and elision processes have been claimed to be categorical rather than gradient (e.g. schwa elision in French, Bürki et al, 2007Bürki et al, , 2010voicing assimilation in French, Hallé & Adda-Decker, 2007; nasal place assimilation in Spanish and Italian, Farnetani & Bus a (1994a,b); Honorof, 1999; /s/ to /P/ accommodation in English, Nolan, Holst, & Kuhnert (1996); place assimilation in Korean, Kochetov & Pouplier (2008), among others). There is therefore evidence that connected speech reduction phenomena may be both gradient and categorical.…”
Section: Contents Lists Available Atmentioning
confidence: 99%